KARAKTERISTIK STRUKTUR DAN SIFAT KIMIA PRODUK BIOGENIK RAYAP SCHEDORHINOTERMES SPP DARI CAMPURAN LIMBAH KERTAS KORAN DENGAN LIMBAH PENGOLAHAN TAHU - Andi Sri Rahayu Diza Lestari A; Musrizal Muin; Astuti Arif (Forestry Faculty of Universitas Hasanuddin, 2019)
Biological activity of termites consistently generates various biogenic products depend of the type of food sources. Furthermore, the biogenic product is believed to have an important role in the improvement of soil physical and chemical properties. The purpose of this study is to determine the structure and chemical properties of biogenic products resulted from the activity of termites Schedorhinotermes spp. using newsprint paper and tofu processing wastes as food sources. Newsprint paper waste was mixed with tofu processing wastes water at a different levels, i.e. 10 %, 20 %, and 30 % (w/v) for the objective of study. Each of the mixture with weight of 18,8 g equivalent to oven dry weight was then placed in the sample container unit size 6 x 6 cm, placed at about 3 cm underground with the indicated of termite Schedorhinotermes spp activity, and covered by PVC stopper. The testing unit were left in place for about 6 weeks to allow the termite attacks. The attacked sample unit were then analyzed for their structure and chemical properties including bulk density, aggregate fraction distribution, pH, C-organic content. The soil around the sample unit were took using a 7 cm diameter ground ring to be used as a reference or comparison with biogenic structures formed by termites. The result showed that the biogenic products have better structure and chemical compared to the its surrounding soil.